Integrating QUIZIZZ into Arabic Language Teaching: Uses and Educational Implications - Gofur, Abdul; Aedi, Khasan; Syamsu, Pradi Khusufi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The development of digital technology, although encouraging the adoption of gamification-based platforms in education, has not yet seen much research conducted to determine their effectiveness and challenges in Arabic language learning. Quizzes are one of the more popular platforms, currently offering real-time scoring and leaderboards as part of the learning experience. Therefore, this study aims to analyze the motivation, effectiveness, and challenges in using Quizizz for Arabic language learning at MAN 1 Cirebon. This study uses a qualitative approach with a phenomenological method involving five students selected through purposive sampling. Data were collected through in-depth interviews and analyzed using the interactive model of Miles, Huberman, and Saldana. The research results show that the use of Quizizz can enhance student motivation through competitive elements, enrich subject understanding in a more enjoyable way, and create activity in the classroom environment. However, there are serious challenges such as limited internet access, data quotas, imperfect devices, and time constraints as obstacles in its implementation. The implication of this research is that the integration of gamification platforms must also consider the readiness in terms of technological infrastructure and the psychological factors of learners to achieve the best results in education. Recommendations in this study include enhancing flexible features and exploring more interactive platforms to adapt to the needs and characteristics of students in different learning contexts.